Criteria of mens rea in the International criminal court (2010)
The Rome Statute of the International Criminal Court (ICC) in its 30th article expresses the necessary elements of the culpability principle, in order to establish the judgement of mens rea of international crimes. The requirement of “Intent and Knowledge